INDRALUPTA (ALOPECIA AREATA): A CASE SUCCESSFULLY TREATED WITH JALUKAVCHARANA (LEECH THERAPY) - Bhavanbhai Shah, *Aaditya; Mohod, Poonam (International Journal of Ayurveda and Pharma Research, 2019)
Hair disorders cause negative impact towards the individual and his/her quality of life. Indralupta is a Kshudraroga characterized by loss of hair. It can be correlate with alopecia areata, which is having chief complaint of hair loss on body especially on scalp without any clinical inflammatory signs. Raktamokshana is a technical term employed to denote a para-surgical procedure to expel out the vitiated blood from selected areas of the body, by specific methods. Ayurveda classical text propounds practical guidelines for bloodletting and claims it as most effective therapy in half of the body ailments. Jalaukavacharna Karma (Leech therapy) is considered as the ideal method to expel out the vitiated blood safely, quickly, and effectively. Here a case of Indralupta (alopecia areata) successfully treated with Ayurveda Raktamokshana treatment is recorded.